HEGEMONI KEKUASAAN DALAM PUISI “AKU TULIS PAMFLET INI” KARYA W.S. RENDRA: KAJIAN ANTONIO GRAMSCI - Friscila Sinaga; Elizabeth Sinaga; Novriana Sitanggang; Yohantio Panta Ria Sihite; Renta Giofani Hutapea (PT. Intelek Cendikiawan Nusantara, 2025)
Puisi